Rabindranath Tagore's drama in the perspective of Indian Theatre - Renganathan, Mala; Bhattacharya, Arnab (London, UK Anthem Press, 2020)
"On 1 January 1877, the title of 'Empress of India' was conferred upon Queen Victoria. To mark the occasion, Sourindramohan Tagore (1840-1941) composed a song in her honour, hailing her as 'rajrajeshwari' [empress]. A month later, the not-yet-sixteen Rabindranath sounded a defiantly different note in a poem, 'Dillir Darbar'"-- Provided by publisher.
Keywords: Theater -- India -- History